Hot filament chemical vapor deposition temperature field optimization for diamond films deposited on silicon nitride substrates - Wu, Yuhou; Zhang, Huisen; Yan, Guangyu; Liu, Lusheng; Cristea, Daniel; Wang, He; Yang, Yumiao; Shen, Jianhui (IOP Publishing, 2021)
The influence of some key parameters of hot filament chemical vapor deposition (HFCVD) on the temperature distribution during the deposition of diamond coatings on silicon nitride (Si3N4) substrates was assessed with the help of the finite element method. Solid heat transfer, fluid heat transfer and surface radiation heat transfer mechanisms were used to calculate the substrate temperature in the steady state during the deposition process. The accuracy of the model was verified by comparing the simulation model with experimental measurements. The comparison shows that the deviation between the model and the actual substrate temperature measurements is within 3%. Furthermore, a Taguchi orthogonal experiment was designed (3 factors, 3 levels, L9). By changing the number of hot filaments, the distance between the filaments and the substrate, and the separation between two adjacent hot filaments, the influence trend of these parameters on the substrate temperature was assessed, leading to an optimal hot filament arrangement. A deposition experiment was carried out using the optimized parameters, and the results showed that the substrate surface temperature obtained by numerical simulation is highly consistent with the temperature measured by the infrared thermometer. The optimized deposition parameters contributed to a more suitable temperature range and more uniform temperature distribution on the Si3N4 ceramic substrate. The deposited diamond film exhibited uniform crystal quality and grain morphology, thus verifying the validity of the simulation results.
Keywords: HFCVD; Si3N4 ceramics; diamond film; numerical simulation